An Investigation into Using Ultrasound for Airway Humidification - Uddin, Riaz (Auckland University of Technology, 2023)
Humidification is an essential process required in many lungs therapeutic devices to overcome the complications caused by dry air in the lungs. The humidification requirements for medical devices are quite different from those for currently available ultrasonic humidifiers. For breathing devices, humidifiers need to produce vapours with droplets of less than 1 µm in diameter, while all other ultrasonic droplet generation devices reported to date cannot consistently generate required diameter droplets. The existing humidifier mechanisms for medical devices are traditional heat transfer devices that add bulky circuitry to the system. The required vaporisation for lung therapeutic devices can be achieved through accelerated evaporation using high-intensity ultrasound impact on droplets. This study explores an alternative approach for generating a strong ultrasonic field that can facilitate the rapid evaporation of droplets, a key requirement for human airway humidification in therapeutic devices such as the Continuous Positive Airway Pressure (CPAP) device. The technique involves applying high-intensity ultrasound to droplets to accelerate their evaporation. The ultrasonic levitation mechanism uses high-intensity ultrasound that can hold droplets. By precisely controlling the frequency and intensity of the ultrasound waves, it can also be used to effectively impact droplets during evaporation if placed as the second stage ultrasonic field. Various options for high-intensity ultrasound field transducers were researched, and with the aid of theoretical investigation and CAD with FEA analysis, the design of a levitator was formed and implemented. The levitator's output was measured, and its interaction with droplets was experimented. The results provide the significant impact of the ultrasonic field on droplets accelerated evaporation. The research has proposed a novel design for an ultrasonic humidifier that can be used in human airways and will help reimagine humidifiers for CPAP systems. It will aid in decreasing the size of the humidifier, which will allow better equipment mobility and improve power efficiency. Ultrasonic humidifier studies will not be restricted to the humidification and miniaturization of the CPAP system but will also help in redesigning humidification systems for other relevant respiratory therapy equipment, such as ventilators.